The Snack thief - Camilleri, Andrea; Sartarelli, Stephen, 1954 -tr. (London : Picador, 2004)
When an elderly man is stabbed to death in an elevator and a crewman on a fishing trawler is gunned down, Inspector Montalbano suspects a link between the two incidents and sets out to find the truth.
Keywords: Homicide -- Fiction; Murder -- Fiction